PENERAPAN SISTEM KEUANGAN DESA (SISKEUDES) TENTANG LAPORAN REALISASI ANGGARAN DANA DESA (STUDI KASUS : KANTOR DESA LASIAI KECAMATAN SINJAI TIMUR KABUPATEN SINJAI) - Ahri Yadi; Muh Akbardin; Djafar (Paser Institute Of Accounting and Finance, 2023)
The purpose of this study The purpose of the study was to determine the application of the village financial system (SISKEUDES) in reporting the realization of the village fund budget for Lasiai, East Sinjai District, Sinjai Regency. The type of research used in this research is quantitative research. The analytical method that will be used in this study is descriptive qualitative, namely where the form of understanding analysis is carried out by describing phenomena or conditions socially in analyzing data to be able to provide information and understanding related to the subject matter in detail and systematically. The results of this study indicate that based on the launch of the siskeudes application version 2.0.5, Lasiai Village also uses the siskeudes application version 2.0.5, because this version has become an appeal from the government to all villages in Sinjai district.